Digital attachment: how fear of missing out and narcissism lead to Instagram addiction - Allo, Silva Linggi; Rahmah, Dian Dwi Nur (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study aims to examine the influence of fear of missing out (FoMO) and narcissism on Instagram addiction. This study was conducted using a quantitative approach. The respondents were 100 students of Faculty of Forestry at X University, selected using a purposive sampling technique. Data were collected through the Instagram addiction scale, which was adapted from the Bergen Social Media Addiction Scale (BSMAS), the Single Item FoMO Scale, and the Narcissistic Grandiosity Scale. Data were subsequently analyzed using multiple linear regression analysis. Results showed that FoMO and narcissism simultaneously influence Instagram addiction. FoMO and narcissism partially have a significant influence. Higher levels of FoMO or narcissism were associated with more severe addiction to Instagram, and vice versa. Results suggest that higher education institutions may benefit from intervention programs, such as trainings on self-management and social media use